Family Communication Patterns and Parental Burnout: A Qualitative Study of Indonesian Mothers of Preschool-Aged Children in Bandung - Tasya Aulia Febriyanti; Rita Destiwati; Ilham Medal Junjunan (PT. Global Research Collaboration, 2026)
Parental burnout among mothers of preschool-aged children is a growing public health concern in Indonesia, exacerbated by entrenched gender norms and limited access to emotionally supportive family environments. This study examines how family communication patterns, specifically through the dimensions of conversation orientation and conformity orientation, influence the psychological resilience of first-time mothers experiencing moderate parental burnout. A descriptive qualitative design was employed within an interpretive paradigm. Data were collected through in-depth interviews, non-participant observation, and documentation involving three primary informants (mothers, n=3), three supporting informants (family members, n=3), and one expert informant (clinical psychologist, n=1) in Bandung, Indonesia. The Family Communication Patterns Theory (FCPT) by Koerner and Fitzpatrick (2002) served as the analytical framework. Data were analysed using Miles and Huberman’s interactive model and validated through source triangulation and member checking. Open conversation orientation serves as the primary protective factor by providing space for emotional validation and preventing the suppression of feelings. Conversely, high conformity orientation characterised by rigid parenting standards tends to generate guilt and impede mothers’ access to emotional support. Non-judgmental, open family communication is the core protective mechanism against the escalation of moderate parental burnout. Strengthening spousal communication quality, increasing flexibility in family norms, and fostering emotionally validating family environments are recommended as strategic priorities for practitioners, community health workers, and policymakers supporting maternal mental health in Indonesia.